Zero-structured matrix modifications keeping essentially unaltered sets of eigenvalues - S. Noschese (Rendiconti di Matematica e delle Sue Applicazioni, 2007)
We show how to construct zero-structured matrices that modify a given matrix A keeping essentially unaltered a selected set of eigenvalues. An accurate report on a significant collection of numerical tests is included. Applications to the study of the behavior of the inherent error are discussed.